How diverse is child language acquisition research?. Issue 6 (December 2022) - Kidd, Evan; Garcia, Rowena
A comprehensive theory of child language acquisition requires an evidential base that is representative of the typological diversity present in the world's 7000 or so languages. However, languages are dying at an alarming rate, and the next 50 years represents the last chance we have to document acquisition in many of them. Here, we take stock of the last 45 years of research published in the four main child language acquisition journals: Journal of Child Language, First Language, Language Acquisition and Language Learning and Development . We coded each article for several variables, including (1) participant group (mono vs multilingual), (2) language(s), (3) topic(s) and (4) country of author affiliation, from each journal's inception until the end of 2020. We found that we have at least one article published on around 103 languages, representing approximately 1.5% of the world's languages. The distribution of articles was highly skewed towards English and other well-studied Indo-European languages, with the majority of non-Indo-European languages having just one paper. A majority of the papers focused on studies of monolingual children, although papers did not always explicitly report participant group status. The distribution of topics across language categories was more even. The number of articles published on non-Indo-European languages from countries outside of North America and Europe is increasing; however, this increase is driven by research conducted in relatively wealthy countries. Overall, the vast majority of the research was produced in the Global North. We conclude that, despite a proud history of crosslinguistic research, the goals of the discipline need to be recalibrated before we can lay claim to truly a representative account of child language acquisition.